2022
DOI: 10.1039/d1cp05894k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple 2D crystal structures in bilayered lamellae from the direct self-assembly of 3D systems of soft Janus particles

Abstract: Numerous crystals and Frank-Kasper phases in two-dimensional (2D) systems of soft particles have been presented by theoretical investigations. How to realize 2D crystals or Frank-kasper phases by direct self-assembly of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 58 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…In this respect, Janus particles (JPs) with two different domains on their surfaces represent an important field of research. Numerous experimental studies of JPs have been complemented by a range of theoretical works devoted to the analysis of self-assembled structures and phase diagrams. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this respect, Janus particles (JPs) with two different domains on their surfaces represent an important field of research. Numerous experimental studies of JPs have been complemented by a range of theoretical works devoted to the analysis of self-assembled structures and phase diagrams. …”
Section: Introductionmentioning
confidence: 99%
“…Rosenthal et al have studied the aggregation of amphiphilic Janus particles in bulk phases and shown that an increase in the system density causes the formation of different aggregates, from spherical micelles, through icosahedrons to huge elongated structures. The recent simulations have suggested a simple route toward 2D crystals via the direct self-assembly of 3D systems of amphiphilic JPs that spontaneously formed ordered bilayered lamellae. Within each layer of the bilayered lamellae, abundant highly ordered 2D crystals including the Frank–Kasper phases and open kagome lattice were observed …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations